Bullying in Buddhism Perspective - Ngamchaiyaphum, Mae Chee Prakrong (Journal of Thammawat, 2020)
Bullying in Buddhism perspective was a problem occurred before Buddha era as evidence in Tripitaka, named Aggañña Sutta, indicated that the first bullying issue was about skin. At present, the situation analysis showed that the bullying could be classified into 4 types: Physical Bullying, Speech Bulling, Social and Emotional Bullying, and Cyberbullying. These was analyzed that they matched with 2 Buddhist dharma principles: 1) Unwholsome Roots 3 because causes of bullying was rooted from greed, hatred, and delusion minds; and 2) Unwholesome Course of Action (false view; wrong view) because they matched with 10 bad karmas which was identified into 3 categories. They are: 2.1) Three Bad Physical Actions – Hitting, Threatening to get asset, and Sexual harassment; 2.2) Four Bad Speech Actions – Lying, Reviling, Slandering, and Mocking; 2.3) Three Bad mental Actions – Greed, Maliciousness, immorality by badly thinking. If they were more collected in mind, it will lead to the physical and speech bullying later. Therefore, paths for coping with the bullying based on Buddhism are consciousness existence, patience for retortation by explanation on the right time, none of tension or too much anxiety, and choosing to live in good environment and society.